Respostas
respondido por:
5
3x + 2y = 40 3x + 2y = 40
x - 7y = -2 <<< multiplique tudo por -3 -3x + 21y = 6
____________
23y = 46
y = 46/23
y = 2
Substituindo em qualquer equação:
x - 7y = -2
x - 7.2 = -2
x -14 = -2
x = -2 + 14
x = 12
Bons estudos
x - 7y = -2 <<< multiplique tudo por -3 -3x + 21y = 6
____________
23y = 46
y = 46/23
y = 2
Substituindo em qualquer equação:
x - 7y = -2
x - 7.2 = -2
x -14 = -2
x = -2 + 14
x = 12
Bons estudos
samirah2:
obg
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás